A bio‐behavioral intervention combining task analysis with skill‐based training to train toothbrushing among children with intellectual disability. (12th May 2021) - Gaunkar, Ridhima; Gadiyar, Akshatha; Kamath, Vinayak; Nagarsekar, Aradhana; Sanjeevan, Vinita; Kamat, Amita Kenkre
Abstract: Aims: Individuals with intellectual disability (ID) have special health care needs. Teaching self‐care behaviors like toothbrushing helps reduce their dependence on adult caregivers. We present a bio‐behavioral intervention combining task analysis with skill‐based teaching of toothbrushing behavior aimed to promote autonomy in children with various types of ID. Methods: One hundred twenty children with ID enrolled at a special school in the State were included in the study. After baseline measurements using task analysis, four methods were used to train the children ‐ instruction, three‐phase modeling, physical guidance, and descriptive praise. The caregiver was trained and given instructional videos for reinforcement. After 4 weeks, the children were asked to brush their teeth and performance was evaluated. Results: There was increased independence in the performance of toothbrushing behavior, the mild and moderate ID groups showing the most improvement. Steps like oral manipulation of the toothbrush showed the greatest improvement in these groups. The severe ID group showed improvement in certain skills, while requiring assistance for others that demanded dexterity. Conclusion: This intervention can be implemented by special schools and special care dentistry centers to foster autonomy in oral self‐care skills in the mild and moderate ID children, and complemented with other methods for severe ID children.